A Prioritized Test Generation Method For Pair-wise Testing - Yu Wang; Hao Wu; Zhenyu Sheng (Institute of Advanced Engineering and Science, 2013)
The most sufficient test methods are based on a test case set which covers all combinations of parameters. However, the scale of test cases is always too large and their cost cannot be accepted. People will first consider the implementation of critical test cases. Even if the test is terminated suddenly, the test cases of high importance will have been executed. It improves the testing efficiency while securing the detection rate of defect. The contribution of this paper is how to generate pair-wise testing cases with a priority. Firstly, We design formulas to compute the weights of priorities. Secondly, we adopt a greed algorithm to solve the combined testing problems. Furthermore, we integrate the greed strategy into a genetic algorithm which makes the most efficient testing in critical parameters and their sets, and ensures its detection rate of defect under limited resources. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1880